A Bibliometric Overview and Visualization of Fuzzy Sets and Systems between 2000 and 2018. Issue 2 (18th August 2021) - Ohlan, Ramphul; Ohlan, Anshu
ABSTRACT: Fuzzy Sets and Systems ( FSS ) is an influential international journal of fuzzy research. This study provides a bibliometric overview of the publications of FSS from 2000 to 2018. The changes that occurred in the inner structure of this journal are captured by analyzing the bibliometric indicators of 4, 348 publications published therein during the period under study. The time profile of this journal is outlined in terms of the number of publications, citations, h-index, category normalized citation impact (CNCI), and g-index. In addition, the most productive and influential authors, institutions, and countries are identified and analyzed. We visualize and illustrate the cocitations network of authors and links of FSS with other journals by estimating structural indicators using VOSviewer software. The emerging trends in themes of FSS are identified by detecting bursting keywords employing CiteSpace software. It is shown that FSS has strong bidirectional connections with other leading journals of fuzzy research. Over 95% of all documents published in FSS have been cited at least once. The annual values of the CNCI of the works published in FSS are found above unity. Regarding thematic diversity, the social and management sciences research constituted a large share in the documents citing articles published in FSS . The average citations were relatively higher for documents published under green Open Access mode in comparison to the paywall set. The results of the study are useful for understanding the knowledge domains of this journal and promising directions for future research in this field.